1997
DOI: 10.1144/gsl.qjeg.1997.030.p3.04
|View full text |Cite
|
Sign up to set email alerts
|

Pore size distribution and the durability of a porous limestone

Abstract: A comparison of durability estimations based on mercury porosimeter data and experimental salt crystallization tests carried out on Bateig Stone from Alicante, Spain, establish that the main factor in the salt crystallization durability test is the 'ink bottle' pore system, identified by the presence of residual mercury in large pores after porosity testing. In addition, the results suggest that the commonly used indirect durability tests may not be considered a scientific definition of building stone behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 7 publications
2
45
0
1
Order By: Relevance
“…The visual deterioration observed after ageing (Figures 2 and 3) consisted in morphologies similar to those defined in limestone by other authors (50). The Redueña specimens showed dimensional losses essentially around the vertices and edges of the stone cubes (Figure 3a), ranging from 3.0 to 8.0 mm in depth.…”
Section: Influencia De La Anisotropía En La Durabilidad De Las Dolomísupporting
confidence: 70%
See 1 more Smart Citation
“…The visual deterioration observed after ageing (Figures 2 and 3) consisted in morphologies similar to those defined in limestone by other authors (50). The Redueña specimens showed dimensional losses essentially around the vertices and edges of the stone cubes (Figure 3a), ranging from 3.0 to 8.0 mm in depth.…”
Section: Influencia De La Anisotropía En La Durabilidad De Las Dolomísupporting
confidence: 70%
“…The Redueña dolostone, however, was only subjected to seven cycles, for some of the specimens became so severely deteriorated that the test had to be interrupted in light of the risk of total destruction, which would have ruled out any comparison between initial and end test results. Respecto al deterioro visual observado después del envejecimiento (Figuras 2 y 3), se observan morfologías de deterioro similares a las definidas por otros autores en calizas (50). En las probetas de la dolomía de Redueña se observa una pérdida de volumen fundamentalmente de los vértices y aristas de los cubos pétreos (Figuras 3a) entre 3,0 y 8,0 mm desde la superficie.…”
Section: Influencia De La Anisotropía En La Durabilidad De Las Dolomímentioning
confidence: 78%
“…However, different studies have reported different sizes of salt weathering-prone micropores: e.g. pore radius less than 0·05 µm (Steiger, 2005b;Scherer, 2006), 0·1 µm (Ordóñez et al, 1997), 0·5 µm (Punuru et al, 1990;Rossi-Manaresi and Tucci, 1991), 1 µm (Benavente et al, 2004a), 2·5 µm (Fitzner, 1988;Mod'd et al, 1996), and 5 µm (Zehnder and Arnold, 1989). To evaluate the relative infl uence of different sizes of micropores detailed in the above mentioned studies, fi ve sizes of micropores were selected.…”
Section: Rock Types and Petrophysical Propertiesmentioning
confidence: 99%
“…También es importante tener en cuenta que las características de textura pueden influir en la tasa y tipo de procesos de alteración físico-químicos que pueden tener lugar en la dolomía, por lo que podrían estar influyendo también de una manera indirecta en la biorreceptividad de la misma. Por ejemplo, el tamaño del poro condiciona los efectos de la cristalización de las sales (23,24). Se ha visto que esta propiedad intrínseca también condiciona la cinética de capilaridad: la absorción de agua y la porosidad accesible son especialmente relevantes en la alteración llevada a cabo durante los ciclos de hielo-deshielo (25,26).…”
Section: Intracrystalline Penetration (unclassified
“…In addition, these properties affect the rate and type of physico-chemical weathering processes that can take place in dolostone, such that these may also indirectly affect its bioreceptivity. For instance, pore size conditions the effects of salt crystallization (23,24) and/or capillarity kinetics: water absorption and accessible porosity influence in the alteration by freeze-thaw cycles (25,26).…”
Section: Intracrystalline Penetration (mentioning
confidence: 99%